EFFECTIVENESS OF ONLINE LEARNING USING DIGITAL PLATFORMS DURING THE COVID-19 - Nurul Mahmudah (Sean Institute, 2022)
Covid-19 pandemic greatly affected all aspects of life, including the world of education. Learning that used to be done conventionally is now being shifted to online learning. Online learning is divided into two, namely synchronous and asynchronous online learning. The two types of online learning, of course, cannot be separated from the use of digital platforms that are used to support the success of online learning. The aims of this study are to prove the effectiveness of learning using a synchronous digital platform for fourth graders at SDN Mojoroto 4 in the 2020/2021 academic year during the Covid-19 pandemic, and to prove the effectiveness of online learning using asynchronous digital platforms for fourth graders at SDN Mojoroto 4 in the academic year. 2020/2021 during the Covid-19 pandemic. This study uses a quantitative approach with quantitative descriptive methods. Data collection was obtained from questionnaires that had been distributed to fourth grade students at SDN Mojoroto 4 and then processed with SPSS software version 25 for windows. From this study, it was found that the use of synchronous and asynchronous digital platforms was effectively used in online learning.